Management of waterborne pathogens in recreational waters - McManus, Alexandra; Weinstein, P.; Bertolatti, Dean; Devine, B. (IUHPE, 2007)
There are no evidence-based guidelines for the management of accidental faecal releases (AFR) in Australia. A pilot study conducted with public swimming complexes chosen based upon their level of risk during the peak usage periods. Staff who were responsible for water management were involved in the pilot study (n=9 staff members). Data collection was conducted over a four-week period. Each complex had an average of two AFR per week over the past 12 months. It was not uncommon for each complex to have at least one AFR each day over the summer period. In fact, one complex recorded seven AFR in one day in the previous month. The areas most at risk of contamination in each complex were smaller pools (used mainly by toddlers and infants) and hydrotherapy pools. The staff involved in the pilot project indicated their support for the study outcomes as providing a standardised way to effectively and efficiently deal with AFR in public recreational water environments.